The influence of usability and enjoyment on electronic customer relationship management performance in Jordan mobile communication services - Wahab, Samsudin; Jusoff, Kamaruzaman; Al Momani, Khaled Abed Mufleh; Mohd Noor, Nor Azila; Mohd Zahari, Ahmad Suffian (Academic Journals, 2011)
Electronic customer relationship management performance is a comprehensive business and marketing strategy that integrates people, process, technology and all business activities for attracting and retaining customers over the internet and mobile phone to reduce costs and increase profitability by consolidation the principles of customer loyalty. Therefore, the results of electronic customer relationship management performance are repeat purchase, word of mouth, retention, cross buying, brand loyalty and customer satisfaction. The keen competitive in the communication and mobile phone service market place and the increasing numbers of mobile phone users all over the world has influence the researcher to investigate usability and enjoyment as antecedents of electronic customer relationship management performance in mobile phone services industry. Four hundreds and eighty eight set of questionnaires have returned and analyzed. Two factors been tested to investigate the relationship with E-CRM performance. The analysis shows that usability was positively significant towards E-CRM performance. Enjoyment has failed to predict E-CRM performance. Base on the results, it can be concluded that the mobile service provider has to ensure their services fully satisfied their customer usability. Somehow, future research must investigate other factors as the antecedent for E-CRM performance. Other initiative is to consider a model testing in difference context of electronic service to see any generalization on the research result.